DUKUNGAN SOSIAL BERHUBUNGAN DENGAN KESIAPAN BERADAPTASI DENGAN COVID-19 - Dini Sholihatunnisa (LPPM STIKES Kendal, 2022)
The condition of the COVID-19 pandemic has resulted in many victims throughout the world, the rapid transmission without severe symptoms in some people is the cause of the increase in COVID-19 cases, as a result the government must prepare various policies or strategies to tackle and prevent transmission from various disease from Alpha to Omicron. To be able to strengthen community resilience in the face of this pandemic, social support is needed. This study aims to examine the relationship between social support with readiness to adapt toward COVID-19. The method used is a cross-sectional approach. The research population is all people in one of the Rukun Warga in Pamulang District who have tested positive for COVID-19. The total number of complete samples that met the inclusion criteria was 231 people. Data was collected by luring from December 2021 to March 2022. Bivariate analysis results p-value (0.000) <p-value (0.05). Thus, there is a significant relationship between social support and readiness to adapt toward COVID-19.